2004
DOI: 10.1007/s11661-004-0218-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of grain size on low-cycle fatigue behavior of Al-2024 polycrystalline alloy

Abstract: Two different sets of fatigue specimens were heat treated at different times or temperatures to investigate the effect of grain size on the low-cycle fatigue behavior of Al-2024 polycrystalline alloy. Straincontrolled low-cycle fatigue testing with a strain rate of 1 ϫ 10 Ϫ4 s Ϫ1 was conducted at room temperature. The fatigue response of the alloy was evaluated macroscopically in terms of cyclic stress strain response and microscopically in terms of appearance of cyclic slip bands. The cyclic stress strain res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…In terms of fatigue behavior, a substantial amount of investigations have been dedicated to aluminum-copper alloys (2xxx series) in recent years, mostly because of their wide use in the aircraft industry [3,27,28,31,[40][41][42][43][44][45]. In this scientific literature, there are also investigations concerned with AA2519 and AA2219, which is the precursor of AA2519 [31,43,46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In terms of fatigue behavior, a substantial amount of investigations have been dedicated to aluminum-copper alloys (2xxx series) in recent years, mostly because of their wide use in the aircraft industry [3,27,28,31,[40][41][42][43][44][45]. In this scientific literature, there are also investigations concerned with AA2519 and AA2219, which is the precursor of AA2519 [31,43,46].…”
Section: Introductionmentioning
confidence: 99%
“…In this scientific literature, there are also investigations concerned with AA2519 and AA2219, which is the precursor of AA2519 [31,43,46]. Mohamed et al revealed that low cycle fatigue behavior of AA2024 is influenced by the size of grains-the alloy with the grain size of 90 µm exhibited lower saturation stress and longer plateau in cyclic stress strain curve than alloy with the grain size of 150 µm [44]. Pec et al reported that fracture area of 2024-T351 is characterized by the ductile mechanism with two size levels of dimples, which is the result of the presence of large inclusions and fine Al 2 Cu precipitates in the alloy microstructure [47].…”
Section: Introductionmentioning
confidence: 99%
“…In the process of fatigue crack propagation, the coarse second-phase particles also have an effect on the fatigue crack propagation [18]. When fatigue crack propagation encounters with such particles, it will be hindered, resulting in fatigue crack spacing, curvature and other changes, and sometimes even interrupted [19].…”
Section: Analysis and Discussionmentioning
confidence: 99%
“…The LCF behavior of the FDD drawn wire was also better than the HDD wire, even though the GS is smaller for the FDD drawn wire, as the LCF performance is noticed to be enhanced with coarser grain size [182,374]. At an applied stress amplitude of 1170MPa, the average no of cycles to failure (Nf) for the three batches of FDD wire were, 3x10 4 , 8x10 5 and 4x10 6 cycles, whereas it was only 1x10 4 cycles for all the three batches of HDD wire tested.…”
Section: Influence Of Drawing Practice On the Cyclic Behavior Of 50%cmentioning
confidence: 93%
“…It has been proven that finer grain size improves the fatigue crack initiation (FCI) [179,180] in the material and the coarser grain size enhances the fatigue crack growth (FCG) [181] resistance of the material. The influence of grain size on the cyclic deformation in metals has been explained concerning the strain compatibility, because of the grain boundary effects [182,183]. There were major disagreements reported regarding the influence of the grain size to the cyclic behavior in different metals, with some investigations reporting that the reduction of the grain size decreased the cyclic saturation stress [184][185][186] while others reported the opposite effect [187][188][189].…”
Section: Fatigue and Microstructurementioning
confidence: 99%